تشكيل مسرى غشاء بلاستيكي منتقي للباميفللين اعتماداً على الزوج الشاردي فوسفو مولبدات باميفللينيوم لتحديده ضمن المستحضرات الدوائية - معروف محمد; أبودان محمود; نجـاري سـليم (Latakia University Journal -Basic Sciences Series, 2018)
استطعنا تحضير مسرى غشاء بلاستيكي لتحديد هيدروكلوريد الباميفللين Bf-HCl بالاعتماد على فوسفو مولبدات باميفللينيوم (Bf-PM) كمادة فعالة كهربائياً. وجدنا أن المسرى المنتقي للباميفللين Bf-PM10SE يتجاوب بجوار علاقة Nernst بميل مقداره -59.38mV/ΔpCBf للجزء المستقيم المفيد تحليلياً من المنحني العياري الذي يقع ضمن المجال ما بين 1.82-6.67mM من تراكيز Bf-HCl ومجال من قيم pH ما بين 2-7، بحد كشف أدنى مقداره 3.39mM عند درجة الحرارة 25±0.1°C. أجرينا التطبيقات التحليلية المختلفة على هذا المسرى، ووجدنا أنه يُمكن تحديد الدواء في محاليله النقية وفي مستحضره الدوائي المحلي بالتحديد المباشر وفق طريقة الخط العياري. Bamifylline hydrochloride (Bf-HCl) reacts with phosphomolybdate anion as the counter ion to produce Bamifyllinium phosphomolybdate (Bf-PM) ion pair complex. The basic Bf-PM10SE electrode performance characteristics are evaluated. Electrode exhibits excellent potential response properties, showing a stable, linear near-Nernstian response within the concentration range 1.82-6.67mM with a mean calibration graph cationic slope of -59.38mV/ΔpCBf over the pH working range of 2-7, with lower limit of detection (3.39mM), at 25±0.1°C. The presented novel sensor based on Bf-PM10%SE was successfully applied to the potentiometric determination of Bf-HCl at its pharmaceutical preparation.